2004
DOI: 10.1074/jbc.m404497200
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Functional Characterization of a Novel Human Misshapen/Nck Interacting Kinase-related Kinase, hMINKβ

Abstract: Misshapen/NIKs-related kinase (MINK) is a member of the germinal center family of kinases that are homologous to the yeast sterile 20 (Ste20) kinases and regulate a wide variety of cellular processes, including cell morphology, cytoskeletal rearrangement, and survival. Here, we present the cloning and functional characterization of a novel human Misshapen/NIKs-related kinase ␤ (hMINK␤) that encodes a polypeptide of 1312 amino acids. hMINK␤ is ubiquitously expressed in most tissues with at least five alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 43 publications
4
38
2
Order By: Relevance
“…Indeed, misshapen-Nck-interacting (NIK)-related kinase (MINK) is a serine-threonine kinase that binds to Nck (28) and that has been shown to selectively connect the TCR to a signaling pathway leading to negative but not positive selection (29). The results shown in this study linking the conformational change in the TCR with negative selection are in keeping with the proposed role for MINK (29), and they suggest that association of Nck-MINK with the TCR during negative selection depends on a conformational change in the TCR complex.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, misshapen-Nck-interacting (NIK)-related kinase (MINK) is a serine-threonine kinase that binds to Nck (28) and that has been shown to selectively connect the TCR to a signaling pathway leading to negative but not positive selection (29). The results shown in this study linking the conformational change in the TCR with negative selection are in keeping with the proposed role for MINK (29), and they suggest that association of Nck-MINK with the TCR during negative selection depends on a conformational change in the TCR complex.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the caspase-dependent MAP4Ks and MST1/2 activation may not be relevant to the Hippo pathway. A few MAP4Ks, including MAP4K1/4/6, are known to interact with NCK1 (noncatalytic region of tyrosine kinase adaptor protein 1), which is an adaptor protein containing Src homology 2 (SH2) and SH3 domains (Su et al 1997;Ling et al 1999Ling et al , 2001Hu et al 2004). NCK1 is located in the cytoplasm and is involved in Ras-GTPase activation by receptor tyrosine kinases (Ger et al 2011) as well as Rho-GTPase activation and actin cytoskeleton A proposed sequential phosphorylation model of LATS activation by MST.…”
Section: The Regulation Of Lats-activating Kinases Mst1/2 and Map4ksmentioning
confidence: 99%
“…MAP4K4 belongs to the mammalian STE20/MAP4K family. Recent studies have shown that MAP4K4 is associated with cell motility, rearrangement of the cytoskeleton, and cell growth (26)(27)(28). Downregulation of MAP4K4 prevents TNF-a-induced insulin resistance in human skeletal muscle (29), and suppresses systemic inflammation by targeting macrophages (30).…”
Section: Introductionmentioning
confidence: 99%